2001
DOI: 10.1097/00007890-200109150-00032
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-Lymphocyte Antigen 4 Gene Polymorphisms and Susceptibility to Acute Allograft Rejection1

Abstract: These initial observations provide the necessary basis to further investigate the risk stratification of transplant recipients based on specific CTLA4 gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…We have previously demonstrated an association between gene polymorphisms in CTLA-4 and acute rejection in solid organ transplantation (20). We now demonstrate that despite a lack of association with acute rejection, the CTLA-4 +49A/G SNP is associated with a significant reduction in liver allograft survival.…”
Section: Discussionmentioning
confidence: 58%
“…We have previously demonstrated an association between gene polymorphisms in CTLA-4 and acute rejection in solid organ transplantation (20). We now demonstrate that despite a lack of association with acute rejection, the CTLA-4 +49A/G SNP is associated with a significant reduction in liver allograft survival.…”
Section: Discussionmentioning
confidence: 58%
“…In view of this, it is important to investigate possible associations for each specific organ. We have recently demonstrated association with an increased risk of rejection in liver and renal transplant recipients and a microsatellite polymorphism in the CTLA4 gene (20). Two other smaller studies have examined the influence of cytokine gene polymorphisms in liver transplant recipients (21,22).…”
Section: Discussionmentioning
confidence: 98%
“…Slavcheva et al 35 found that long alleles of (AT)n repeats of the CTLA4 gene were associated with an increased risk of acute rejection. It has been suggested that the frequency of long alleles of (AT)n repeats was increased among patients with Wegener's granulomatosis.…”
Section: Discussionmentioning
confidence: 99%